Moderate Glucose Control Is Associated With Increased Mortality Compared With Tight Glucose Control in Critically Ill Patients Without Diabetes - Lanspa, Michael J. (American College of Chest Physicians, 2013)
BACKGROUND: Optimal glucose management in the ICU remains unclear. In 2009, many clinicians at Intermountain Healthcare selected a moderate glucose control (90-140 mg/dL) instead of tight glucose control (80-110 mg/dL). We hypothesized that moderate glucose control would affect patients with and without preexisting diabetes differently. METHODS: We performed a retrospective cohort analysis of all patients treated with eProtocol-insulin from November 2006 to March 2011, stratifying for diabetes. We performed multivariate logistic regression for 30-day mortality with covariates of age, modified APACHE (Acute Physiology and Chronic Health Evaluation) II score, Charlson Comorbidity score, and target glucose. RESULTS: We studied 3,529 patients in 12 different ICUs in eight different hospitals. Patients with diabetes had higher mean glucose (132 mg/dL vs 124 mg/dL) and greater glycemic variability (SD = 41 mg/dL vs 29 mg/dL) than did patients without diabetes (P < .01 for both comparisons). Tight glucose control was associated with increased frequency of moderate and severe hypoglycemia (30.3% and 3.6%) compared with moderate glucose control (14.3% and 2.0%, P < .01 for both). Multivariate analysis demonstrated that the moderate glucose target was independently associated with increased risk of mortality in patients without diabetes (OR, 1.36; 95% CI, 1.01-1.84; P = .05) but decreased risk of mortality in patients with diabetes (OR, 0.65; 95% CI, 0.45-0.93; P = .01). CONCLUSIONS: Moderate glucose control (90-140 mg/dL) may confer greater mortality in critically ill patients without diabetes compared with tight glucose control (80-110 mg/dL). A single glucose target does not appear optimal for all critically ill patients. These data have important implications for the design of future interventional trials as well as for the glycemic management of critically ill patients.